PENTINGNYA APLIKASI PENANGANAN SPYWARE UNTUK KEAMANAN PRIVASI USER PADA SEBUAH KOMPUTER - Bonok, Zainudin (Sainstek, 2011)
Spyware has made a lot of losses, such as using resource illegally and violation of users privacy. Therefore this research is being done with some purpose to implement a good examination file technique for spyware handling application, and to make spyware handling application which can erase spyware file that is found by it. The method which is used in this research is experimental observation by directly doing an experiment in making spyware handling application that used API functions in the searching files method. Also being used are the literature review and observation of the losses that is made by spyware. Furthermore, the analysis for program needs is using UML (Unified Modelling Language) method, then it is implemented using Microsoft Visual Basic 6.0 compiler and being tested using both black box and white box approaches. This research shows that the application which has been made can be used to search for spyware files, stopping process and deleting the spyware file. Keywods: Spayware, Unified Modelling Language